THE FIGHT AGAINST INFECTIOUS DISEASES OF UZBEKISTAN ON EXPERIENCE - Buronov Olim Murodullaevich (Western European Studies, 2024)
Thus, among the population to prevent various infectious kasallaklarning, on the organization of the sanitary service has become one of the priority areas in the development of medicine. Thus, the sanitary-epidemioligiya paid attention to the main activities of the center. As a result of events in the next year out tib preventive and sanitary-epidemiological stability to ensure were achieved
Keywords: Health care; sanitation; epidemiology; prevention